Gas chromatography-mass spectrometry analysis of agarwood extracts from mature and juvenile Aquilaria malaccensis - Jong, Phai Lee; Tsan, Pascale; Mohamed, Rozi (Friends Science Publishers, 2014)
Chemical composition of crude extracts from infected woods of Aquilaria malaccensis were compared to that of healthy wood and commercial agarwood. Infected woods were collected six months after drilling of wild mature trees or after fungal inoculation into the stem of 4-year-old trees. Agarwood substances were extracted in methanol and were subjected to GC-MS analyses. The major compounds were chromone derivative, aromatic compounds, sesquiterpenes, monoterpenes, sterols and fatty acid methyl ester. Aromatic compounds constituted of aldehyde, phenol, ether and ketone groups. In the agarwood extract of the juvenile fungal-elicited tree but not in the healthy wood, some major compounds found were 2-(2-phenylethyl) chromone derivative, 4-phenyl-2-butanone, (1S,4S,7R)-1,4-dimethyl-7-(prop-1-en-2-yl)-1,2,3,4,5,6,7,8-octahydroazulene [guaiene], 1,1,4,7-tetramethyl-2,3,4,5,6,7,7a,7b-octahydro-1aH-cyclopropa[h]azulen-4a-ol [palustrol], and 4-(4- methoxyphenyl) butan-2-one [anisylacetone]. These were also found from agarwood of different grades and agarwood collected from the wild mature tree, in addition to agarospirol, alloaromadendre oxide (2), α-elemol, γ-eudesmol, and guaiol. This work demonstrated that in young A. malaccensis trees, fungi may be associated to the formation of important agarwood compounds and can be detected as early as six months after inoculation.